METHODS AND COMPOSITIONS FOR TREATING POLYOMA VIRUS INFECTION - THOMPSON, Sunnie; JUSTICE, Joshua (2020)
Methods for the treatment of a polyomavirus infection, for decreasing the viral titer of a PyV in a subject having a PyV infection, for treating a adverse effect of a treatment that suppresses the immune system, for inhibiting the DNA damage response pathway, and related methods are provided. Compounds, kits, and composition usefule in the described methods are also provided. Suitable compounds useful in the methods disclosed include inhibitors of ataxia telangiectasia mutated and ATM-Rad 3 related proteins. L'invention concerne des procédés pour le traitement d'une infection par le polyomavirus, destinés à diminuer le titre viral d'un PyV chez un sujet atteint d'une infection par le PyV, à traiter un effet indésirable d'un traitement qui supprime le système immunitaire, à inhiber la voie de réponse à l'endommagement de l'ADN, et des procédés associés. L'invention concerne également des composés, des kits et des compositions utiles dans les procédés décrits. Les composés appropriés utiles dans les procédés décrits comprennent des inhibiteurs de protéines mutées de l'ataxie télangiectasie et de protéines associées à l'ATM-Rad 3.